A controlled trial of heparin therapy in the coagulation defect of paracetamol-induced hepatic necrosis. Issue 2 (February 1974) - Gazzard, B. G.; Clark, R.; Borirakchanyavat, V.; Williams, Roger
Abstract : Treatment of the coagulation disturbances developing with hepatic damage following a paracetamol overdose was assessed in a controlled trial of 22 patients, one half being given heparin and fresh frozen plasma and the other fresh frozen plasma alone. No significant difference was observed either in the speed of correction of the coagulation defect or in the clinical outcome. Two-thirds of the patients had evidence of disseminated intravascular coagulation, but despite the presence of a severe coagulation defect, significant bleeding occurred in only five patients. This may be because with paracetamol-induced hepatic necrosis both the coagulation defect (and possibly other features attributable to severe hepatic insufficiency) are of shorter duration than in hepatic necrosis due to causes such as viral hepatitis in which the liver damage may be a continuing process.